(untitled) - Steven A Beebe (New Jersey)
The book contains 5 parts. Part 1: Introduction to Public Speaking. Part 2: Overview of the Speechmaking Process. Part 3: Listening to Others. Part 4: Analyzing the Audience. Part 5: Developing Your Speech
Keywords: public speaking